Perfectionism and anxiety sensitivity as predictors of trait anxiety - Lauri Korajlija, Anita; Jokić-Begić, Nataša (2011)
The Integrative Hierarchical Model of Anxiety ( Brown, Chorpita, and Barlow, 1998) postulated that any anxiety disorder can be described by a combination of general (common to all disorders), specific (connected with several disorders) and unique (connected only to a specific disorder) factors. The aim of this study is to examine the relationship between the general vulnerability factors of trait anxiety and the specific vulnerability factors of anxiety sensitivity and perfectionism. Mixed method explanatory design was used.The quantitative study was conducted on a normative non-clinical adult sample (N=1061). In the qualitative part of the research seven persons with anxiety disorders were interviewed. The results showed that anxiety sensitivity and perfectionism were significant predictors of trait anxiety with significant gender differences in the structure of the predictors. Dimensions of anxiety sensitivity and perfectionism together explained 55.9% of trait anxiety variance in adult women. Dimensions of anxiety sensitivity and perfectionism together explained 46% of trait anxiety variance in adult men. Qualitative part of the study confirmed significant role of perfectionism and anxiety sensitivity in appearance and persistence of anxiety symptoms. The results confirm that anxiety sensitivity and perfectionism were significant risk factors for trait anxiety and we can conclude that these are predictors which should be kept in mind in dimensional approaches to anxiety
Projekt MZOS
ENG